Patient and provider barriers, facilitators, and implementation preferences of intimate partner violence perpetration screening - Galina A. Portnoy; Richard Colon; Georgina M. Gross; Lynette J. Adams; Lori A. Bastian; Katherine M. Iverson (BMC, 2020)
Abstract Background The substantial prevalence and consequences of intimate partner violence (IPV) underscore the need for effective healthcare response in the way of screening and follow up care. Despite growing evidence regarding perspectives on healthcare-based screening for IPV experiences (i.e., victimization), there is an extremely limited evidence-base to inform practice and policy for detecting IPV use (i.e., perpetration). This study identified barriers, facilitators, and implementation preferences among United States (US) Veterans Health Administration (VHA) patients and providers for IPV use screening. Methods We conducted qualitative interviews with patients enrolled in VHA healthcare (N = 10) and focus groups with VHA providers across professional disciplines (N = 29). Data was analyzed using thematic and content analyses. Results Qualitative analysis revealed convergence between patients' and providers' beliefs regarding key factors for IPV use screening, including the importance of a strong rapport, clear and comprehensive processes and procedures, universal implementation of screening, and a self-report screening tool that assesses for both IPV use and experiences concurrently. Conclusions Findings provide foundational information regarding patient and provider barriers, facilitators, and preferences for IPV use screening that can inform clinical practice and next steps in this important but understudied aspect of healthcare.